Sequential Therapy with Azelastine in Seasonal Allergic Rhinitis - Kremer, Bernd; Klimek, Ludger; Gülicher, Dirk; Degen, Monika; Mösgesc, Ralph; null (Arzneimittelforschung, 1999)
A sequential therapy treatment with azelastine (Allergodil®) in seasonal allergic rhinitis is introduced. In the critical early stage, treatment begins with a combination of azelastine tablets (azelastine hydrochloride, CAS 79307-93-0) and azelastine nasal spray (azelastine, CAS 58581-89-8), and after five days only the nasal spray is administered. This sequential therapy model aims at achieving the quickest and most complete effect without reducing the tolerability. The investigation was carried out as a randomized, controlled double-blind phase IV study of parallel group design with 300 patients during 14 days. In the first five days, one group was given one puff (0.14 mg) of azelastine nasal spray twice daily and one 2 mg tablet of azelastine at night. The other group received nasal spray and a placebo tablet. Beginning on day six, both groups received nasal spray only. Both treatments proved to be effective; the combination therapy, however, was significantly more effective beginning as early as the first treatment. The superiority of the combination therapy increased until day five. Thereafter, the two curves grew closer together; however, the superiority of the combination treatment remained. The tolerability of both treatments was similar.
Keywords: Allergic rhinitis; Allergodil®; efficacy, Phase IV study, sequential therapy; tolerability; Azelastine; CAS 58581-89-8; CAS 79307-93-0